Prevalence of urinary tract infections, associated risk factors, and antibiotic resistance pattern of uropathogens in young women at Noakhali, Bangladesh - Hossain, Imam; Bhowmik, Sutapa; Uddin, Mohammad Sharif; Devnath, Popy; Akter, Asma; Eti, Lutfun Nahar; Hussen, Shakhawat; Rahman Nayem, Mohammad Maksudur; Rahman, Shahidur; Sayem, SM; Islam, Md Towhidul (Asian Journal of Medical and Biological Research, 2021)
Urinary tract infection (UTI) remains one of the most common infections among young females diagnosed in developing countries. The emergence of antibiotic resistance among uropathogens is a global problem. This study aimed to determine the prevalence and resistance of antibiotics to uropathogens, and to understand the relationship of uropathogens to multiple clinical, social and demographic factors of young female students in a university in Bangladesh. Four hundred freshly voided midstream urine samples collected from young female students and several clinical and socio-demographic variables along with UTI symptomatic queries were determined. Bacterial isolation was carried out by using standard and specific microbiological techniques and antimicrobial susceptibility pattern was determined by Kirby Bauer Disc diffusion method. Among the tested specimens, 106 (26.5%) has significant bacterial growth, 60 (57%) were symptomatic, and 46 (43%) were asymptomatic. The highest uropathogen was recorded within the age group of 24-25 years (51%). There was a significant association (p < 0.05) of uropathogen with anatomical abnormality of urinary tract, water sources for food preparation and bathing, and the number of person sharing the same toilet. Most predominantly isolated bacteria were E. coli (32.08%) followed by Staphylococcus saprophyticus (24.53%), Streptococcus spp. (16.04%), Klebsiella spp. (14.15%), Aceinetobacter spp. (4.72%), Citrobacter spp. (2.83%), Enterobacter spp. (2.83%), and Pseudomonas spp. (2.83%). In the effectiveness of each treated antibiotic, urinary pathogens were highly resistant towards nalidixic acid (80.19%), ampicillin (75.73%), cephalexin (70%) and azithromycin (68.48) while against imipenem (7.94%) and amikacin (18.87%) least resistancy were found. A good understanding of the etiology of uropathogens will assist the general practitioner to identify the correct therapeutic strategy for the proper management of UTIs. Asian J. Med. Biol. Res. 2021, 7 (2), 202-213